THE ARAL SEA’S ECOLOGICAL, SOCIAL, AND ECONOMIC PROBLEMS - J.A. Ro‘ziev (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The Aral Sea is a large inland water body located in Central Asia and had significant ecological and economic importance until the mid-20th century. However, the redirection of water from the Amu Darya and Syr Darya rivers to irrigation systems caused the sea level to drop sharply, its area to shrink, and an ecological crisis to emerge. This article scientifically analyzes the Aral Sea’s drying, salinization, water quality deterioration, the impact on fisheries and agriculture, as well as the social and health problems for the local population. In addition, ecological restoration and international cooperation measures are discussed, and ways to reduce the problem through rational management of water resources, soil, and climate monitoring are recommended.